Progress in the implementation of the OpenAIRE guidelines for CRIS managers - de Castro, Pablo (2017)
This contribution provides an update on the implementation of the OpenAIRE Guidelines for CRIS Managers based on CERIF-XML, which aim to allow Current Research Information Systems (CRIS) to be harvested by the OpenAIRE content aggregator. Besides describing the technical challenges posed by this step forward in system interoperability, the text provides an insight on the CRIS landscape and how different systems could gradually become OpenAIRE-compliant. The contribution is a follow-up to previous presentations on the progress with the drafting of these guidelines that were delivered at past CRIS conferences.